Establishing Processing Priorities: Recommendations from a 2017 Study of Practices in US Repositories. Issue 1 (3rd April 2018) - Cooper Cary, Amy; Hackbart-Dean, Pam
Abstract: Building upon archival scholarship and previous solutions addressing backlog collections, this study seeks to identify a comprehensive, integrated, and effective strategy to establish and maintain processing priorities. This study is based on supporting research, which includes the results of a survey of archivists and the findings of five focus group discussions about processing priorities. Using these findings, the authors (a) consider whether this focus on an old problem has motivated archivists to find innovative solutions; (b) determine whether archivists are using these tools; (c) consider whether and how archivists have changed processing priority practices and policies; and (d) seek to clarify current metrics to establish overall processing priorities.